PERANCANGAN MESIN PENGUPAS TEMPURUNG KELAPA MENGGUNAKAN SOFTWARE FEM - herdiana, ade; Riyadi, Slamet (Universitas Majalengka, 2022)
Commodity coconut (Cocos Nucifera L) is a plantation crop that has a very large contribution to the Indonesian economy. Coconut plantations have the second largest area in Indonesia after oil palm plantations. Coconuts are widely cultivated, used and utilized by the community for various purposes and coconuts are the most widely used part. Coconut fruit is processed into various types of food, beverages, cooking and raw materials for making oil (copra). To produce copra and coconut milk, the coconut fruit is separated first between the pulp and coconut shell. For the production of coconut milk, stripping the shell is useful to maintain the purity of the coconut milk. The process of peeling coconut shells/coconut shells manually or mechanically is considered less effective because this method of grating makes the remaining shells also shredded so that this affects the quality of coconut milk. Also the process of peeling coconut shells / coconut shells manually is very dangerous for fear of injuring members of the hand. in research begins with planning to identify problems as well as collect data. Product concept to determine the function and overall structure depicted by block diagrams. The design process is carried out using CAD software which produces design drawings specifically in the form of design information before entering the production process. The coconut shell peeler machine is made with an electric motor used 1HP, with motor power (P) = 746 W, motor shaft rotation (n) = 1445 rpm, and electric motor voltage (V) = 220 Volts. The stripping process on the machine is equipped with 1 blade, with 1 rotating gear, which is attached to the rotating shaft which is driven by an electric motor. The knife material used is SKD 11 steel. The overall dimensions of the coconut shell peeler machine are 550 mm long, 400 mm wide, and 850 mm high.